From the colony of Japan to the successful implementation of the japanese development model: Traces of Japan in the developmentalist political economy of south Korea - ÖKTEN, NİLAY; AL, ARZU (My University, 2022)
While this study examines the effect of the colonial past on post-independence institutions on the JapanSouth Korea axis through the experience of developmentalist political economy, it focuses on the application of the Japanese development model in the post-independence political economy of South Korea, a former Japanese colony, and detects the traces of Japan in the country’s political economy. An exemplary study was conducted on how the colonial heritage felt itself in the social and economic structures established during and after the new state building, and how Korea was built on this colonial legacy with independence that came after years of control by Japan, and to what extent the colonial history was influential in the country’s political economy. Within the scope of this study, while focusing on Japan’s legacy in the Korean political economy, it is also aimed to include a comparative political economy perspective of the study with references to the world colonial history. The study mainly identifies the Japanese heritage in the history of South Korea's political economy, and identifies the traces of Japan in the success of South Korea, which emulates Japanese developmentalism in post-independence political economy. While the legacy of the infrastructure of the colonial period remains in one place, a theoretical discussion is carried out on the Japanese model, whose traces we see in a different dimension in the political economy of South Korea, with the adoption of the developmentalist model of Japan after independence.

Bu çalışma, kalkınmacı ekonomi politik deneyim üzerinden kolonyal geçmişin bağımsızlık sonrası kurumlardaki etkisini Japonya-Güney Kore ekseninde incelerken Japonya kolonisi olan Güney Kore’nin bağımsızlık sonrası ekonomi politiğindeki Japon kalkınma modelinin uygulanmasına odaklanarak ülkenin ekonomi politiğinde Japonya izlerini tespit etmektedir. Sömürgeci mirasın, yeni devlet inşası aşamasında ve sonrasında kurulan toplumsal ve ekonomik yapılarda kendini hissettirmesi ve Japonya’nın kontrolünde geçirdiği yıllardan sonra, bağımsızlıkla birlikte Kore’nin, bu sömürge mirası üzerine nasıl inşa edildiği ve sömürge tarihinin, ülkenin ekonomi politiğinde ne ölçüde etkili olduğu üzerinden bir örnek araştırma yürütmüştür. Bu çalışma kapsamında Japonya’nın Kore ekonomi politiğindeki mirasına odaklanırken bir yandan da dünya sömürge tarihine atıflarla çalışmanın karşılaştırmalı bir ekonomi politik perspektifi içermesi hedeflenmektedir. Çalışma temel olarak Güney Kore’nin ekonomi politik tarihinde Japon mirasını belirlemekte ve bağımsızlık sonrası ekonomi politikte Japonya kalkınmacılığına öykünen Güney Kore’nin başarısında Japonya izlerini tespit etmektedir. Sömürge dönemindeki alt yapıların mirası bir yerde durmaktayken, bağımsızlık sonrasında Japonya’nın kalkınmacı modelinin benimsenmesiyle Güney Kore’nin ekonomi politiğinde farklı bir boyutta izlerini gördüğümüz Japonya modeli üzerinden teorik bir tartışma yürütülmektedir
Japonya kolonisinden Japon kalkınma modelinin başarılı uygulayıcılığına: Güney Kore’nin kalkınmacı ekonomi politiğinde Japonya izleri
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Güney Kore; Japon Sömürgeciliği; Chaeboller; Kalkınma; Ekonomi Politik; South Korea; Japanese Colonialism; Chaebols; Development; Political Economy